Combination of Repetitive Transcranial Magnetic Stimulation on the left Dorsolateral Prefrontal Cortex with Repetitive Peripheral Magnetic Stimulation Reduces Pain Scale in Patients with Chronic Low Back Pain - Rahmadhani, Rauly; Andi Kurnia Bintang,; Andi Weri Sompa,; Rina Masadah, (Alami Journal (Alauddin Islamic Medical) Journal, 2023)
Prevalence of chronic low back pain (CLBP) is still high, there is no effective pharmacological treatment with minimal side effects when consumed in the long term, while the treatment of CLBP generally requires long-term pain treatment. This study aims to assess the effect of a combination of repetitive Transcranial Magnetic Stimulation (rTMS) and repetitive Peripheral Magnetic Stimualtion (rPMS) on pain scale changes in patients with CLBP. This is an experimental study using consecutive sampling which is divided randomly into two groups. The treatment group received pharmacology treatment and combination of rTMS and rPMS for two weeks, the control group was only given pharmacology treatment. Pain was measured in both groups on the first, sixth, and thirteenth days. The results showed that there was a significant difference in pain reduction between the treatment group and the control group. The decrease in pain scale in the treatment group was much greater with a mean value of -6.07 compared to the control group with a value of -3.00, significant with a p value of 0.001. Conclusion: After 10 intervention sessions the combination of rTMS and rPMS had an effect on reducing the pain scale in patients with chronic low back pain.